IgA subclasses have different effector functions associated with distinct glycosylation profiles - Steffen, Ulrike; Koeleman, Carolien A.; Sokolova, Maria V.; Bang, Holger; Kleyer, Arnd; Rech, Jürgen; Unterweger, Harald; Schicht, Martin; Garreis, Fabian; Hahn, Jonas; Andes, Fabian T.; Hahn, Madelaine; et al. (Nature Communications, 2020)
Monomeric serum immunoglobulin A (IgA) can contribute to the development of various autoimmune diseases, but the regulation of serum IgA effector functions is not well defined. Here, we show that the two IgA subclasses (IgA1 and IgA2) differ in their effect on immune cells due to distinct binding and signaling properties. Whereas IgA2 acts pro-inflammatory on neutrophils and macrophages, IgA1 does not have pronounced effects. Moreover, IgA1 and IgA2 have different glycosylation profiles, with IgA1 possessing more sialic acid than IgA2. Removal of sialic acid increases the pro-inflammatory capacity of IgA1, making it comparable to IgA2. Of note, disease-specific autoantibodies in patients with rheumatoid arthritis display a shift toward the pro-inflammatory IgA2 subclass, which is associated with higher disease activity. Taken together, these data demonstrate that IgA effector functions depend on subclass and glycosylation, and that disturbances in subclass balance are associated with autoimmune disease.
CRIS-Team Scopus Importer:2020-01-21